Mechanisms of Damage Involved in Small Intestinal Tract Caused by Nonsteroidal Anti-Inflammatory Drugs - Chávez-Piña, Aracely Evangelina; Abril-Urías, Reyes Roderico; Cerecedo, Doris (Mexican Journal of Medical Research ICSA, 2018)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are among the most commonly used type of drugs, as they are very effective as antiinflammatory, anti-pyretic and analgesic. Their use has increased dramatically over the years even without a medical prescription¸however the use of NSAIDs is limited due to the adverse effect in the gastrointestinal tract, heart and kidney. This research work is focused on the adverse effect in the gastrointestinal tract. The mechanisms involved in gastric damage caused by NSAIDs are well known compared to those in the intestinal area. Research on NSAID-induced intestinal damage is very limited, despite its higher mortality rate, partially due to the difficulty of reaching this area. Therefore, this review mentions some of the mechanisms involved in small intestinal damage to help as a reference to continue doing research about new strategies to come up with an effective clinical therapy.